Gout management in Swiss primary care – a retrospective observational study (Swiss Medical Weekly, 2020)
BACKGROUND Gout is the most common form of inflammatory arthritis worldwide and its prevalence is rising. In Switzerland, there are no data available on the characteristics and treatment of gout patients. In this study, we aimed to describe numbers of patients affected by gout and hyperuricaemia and unveil approaches Swiss primary care physicians (PCPs) use for the management. METHODS This was a retrospective observational study using electronic medical routine data provided from 242 Swiss PCPs. Included were all their patients receiving urate-lowering therapy (ULT), with a diagnostic code for gout or who had a serum uric acid (SUA) measurement. According to their disease status, patients were classified into four subgroups (normal urate, hyperuricaemia, untreated gout, treated gout). For treatment analysis, patients with SUA measurements before and after ULT initiation were included. Comorbidities and risk factors for secondary causes relevant in the context of gout were collected. Outcomes were prevalence of gout and hyperuricaemia, characteristics of patients according to subgroup, number of SUA measurements, levels of SUA and patients who reached the treatment goal of a SUA level